1992
DOI: 10.1016/s0022-5347(17)37618-8
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Penis. II. Treatment of the Primary Tumor

Abstract: The treatment of the primary tumor in 110 patients with squamous cell carcinoma of the penis seen between 1956 and 1989 was reviewed. Small tumors had generally been treated by penis conserving methods, such as circumcision, local excision and external radiotherapy alone or after circumcision or local excision. Since 1982 we have used the neodymium:YAG laser as a penis conserving method. In 51 patients (46%) penis conserving treatment had been performed and 59 (54%) had undergone some form of amputation. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
1
16

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(73 citation statements)
references
References 29 publications
2
54
1
16
Order By: Relevance
“…The clinical examination of the inguinal lymph nodes tumour with no or minimal histopathological infiltration, and (iii) inflammatory involvement of the scrotum and as a method of determining the presence of metastases had a negative predictive value of 88% and positive pubic area creating the impression of cancerous infiltration [16]. Imaging studies such as cavernosography, predictive value of 72% [16]. Lymphangiography, CT and fine-needle aspiration cytology all have a positive ultrasonography or MRI may be used to assess clinically the degree of local infiltration, but their accuracy has predictive value of 100%, but a negative predictive value of only 40%, 30% and 50%, respectively.…”
Section: Tamentioning
confidence: 98%
See 3 more Smart Citations
“…The clinical examination of the inguinal lymph nodes tumour with no or minimal histopathological infiltration, and (iii) inflammatory involvement of the scrotum and as a method of determining the presence of metastases had a negative predictive value of 88% and positive pubic area creating the impression of cancerous infiltration [16]. Imaging studies such as cavernosography, predictive value of 72% [16]. Lymphangiography, CT and fine-needle aspiration cytology all have a positive ultrasonography or MRI may be used to assess clinically the degree of local infiltration, but their accuracy has predictive value of 100%, but a negative predictive value of only 40%, 30% and 50%, respectively.…”
Section: Tamentioning
confidence: 98%
“…The reasons for this included (i) infection and oedema masking the actual size of the primary However, there were very few patients and the validity of designating all grade 3 tumours as T4 should be tumour and giving a false impression of infiltration, (ii) primary presentation as a large exophytically growing assessed in larger studies. The clinical examination of the inguinal lymph nodes tumour with no or minimal histopathological infiltration, and (iii) inflammatory involvement of the scrotum and as a method of determining the presence of metastases had a negative predictive value of 88% and positive pubic area creating the impression of cancerous infiltration [16]. Imaging studies such as cavernosography, predictive value of 72% [16].…”
Section: Tamentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 We have previously reported that some stage T 2 tumors can be treated to conserve the penis using laser hyperthermia combined with radiation therapy and chemotherapy. 3 In the present study, we report on a case of a penile tumor with regional metastasis that was successfully treated with this combination treatment.…”
Section: Introductionmentioning
confidence: 99%